Pyrosequencing analysis of apical microbiota of teeth with persistent apical periodontitis - Yifan Ping; Juan Wang; Jingping Liang (Elsevier, 2015)
Background/purpose: Bacteria inside and outside the root canal at the apical area are crucial for persistent periapical infection. Thus, we aimed to investigate the composition and diversity of apical microbiota in persistent apical periodontitis lesions. Materials and methods: Twenty teeth with persistent apical periodontitis were recruited in this study. Apical sections of teeth roots were collected from patients during their root-end surgeries. Apical root samples were cryogenically grinded, and DNA was extracted from powder samples and preserved according to protocols for later pyrosequencing analysis. Results: Two thousand two hundred and six bacterial species-level phylotypes (at 3% divergence), 216 genera, and 20 phyla were taxonomically figured out from the pyrosequencing results, among which Firmicutes, Proteobacteria, Bacteroidetes, Fusobacteria, Actinobacteria, Synergistetes, and Spirochaetes are the most representative phyla. Massive interindividual variations were revealed in the components of apical microbiota. Conclusion: Compared with the traditional molecular biological methods, pyrosequencing technique helped to discover an unexpected high bacteria diversity of apical microbiota in this study. The etiology of persistent apical periodontitis is complex due to the heterogeneous communities of bacteria existing in the vicinity.